2019
DOI: 10.22146/agritech.42610
|View full text |Cite
|
Sign up to set email alerts
|

Kinetika Perubahan Sifat Fisik dan Kadar Tanin Biji Sorgum (Sorghum Bicolor L.) Selama Perendaman

Abstract: Some studies have been done to examine that the soaking process of sorghum seeds decrease the tannin level, but have not yet examined the kinetics of reaction changes during soaking. The aim of this experiment was to study the kinetics of changes on physical characteristics and tannin level of sorghum seeds during soaking. This experiment used milled and not milled red sorghum seeds which were soaked for 24 hours in distilled and alkaline solution at 30, 45, and 60 ºC. Observed parameters included water conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
1
0
2
Order By: Relevance
“…By observing the values of R 2 , PE, and RMSE from Table 1, it can be concluded that the change of C, DE, and AE followed the first-order, whereas H o followed the zero-order kinetics equations. This result was in line with the discussion in previous research in which most of the literature stated that the kinetics of the change in food processing tends to follow the first-order patterns [16].…”
supporting
confidence: 92%
“…By observing the values of R 2 , PE, and RMSE from Table 1, it can be concluded that the change of C, DE, and AE followed the first-order, whereas H o followed the zero-order kinetics equations. This result was in line with the discussion in previous research in which most of the literature stated that the kinetics of the change in food processing tends to follow the first-order patterns [16].…”
supporting
confidence: 92%
“…Changes in the bond limit and the treatment period were modeled using the first-order kinetic model equation. Equations 1 to 3 show formula of first-order kinetic equation (Asropi, et al, 2019). where 𝐶 𝑡 : the value of the observed variable at time t, 𝐶 𝑜 : the value of the observed variable when t moves to 0, 𝐶 𝑒 : the value of the observed variable at equilibrium, k: rate of change constant, t: time.…”
Section: Methodsmentioning
confidence: 99%
“…Berdasarkan Tabel 1. terdapat beberapa perbedaan karakteristik dengan literatur. Perbedaan tersebut dapat disebabkan karena perbedaan varietas tanaman (Sastrahidayat dan Hadiastono, 2011), perbedaan metode penanaman, kondisi lingkungan, genetik (Daryono dan Maryanto, 2018), metode penepungan (Asropi et al, 2019) dan metode ekstraksi pati (Alam dan Nurhaeni, 2008).…”
Section: Karakteristik Bahan Bakuunclassified